Should you need an organ… Flemish secondary school students' attitudes toward xenotransplantation and transgenetic organ donation. (30th November 2021) - Reyneke, Maryn; Kerckhof, Nel; Dherwani, Rachna; Borry, Pascal
Abstract: Background: The supply of human organs available for transplantation remains grossly inadequate globally. Animal‐to‐human transplantation, and even more so humanized organ grown in animals, holds promising results for the start of clinical trials in humans. Very little is known about the public's willingness to accept different xenotransplantation techniques. This study aims to determine attitudes toward human‐to‐human transplantation, animal‐to‐human transplantation, and chimera‐to‐human transplantation in the Belgium context. Methods: Secondary school students from Flanders, Belgium, were surveyed between January and June 2019. Socio‐demographic details likely to influence participants' attitudes were gathered. Participants were presented with three hypothetical cases (human‐to‐human transplantation, animal‐to‐human transplantation, and chimera‐to‐human transplantation) and asked about their willingness to accept the particular organ. Their risk appetite to accept organs with potentially worse outcomes than the status quo was also evaluated. Results: Seven hundred forty‐one complete questionnaires were analyzed. It can be concluded that Flemish secondary school students favored the techniques of xenotransplantation to a lesser extent than allotransplantation; however, most of them did consider it a good solution for organ shortage. Compared to animal‐to‐human transplantation, chimera‐to‐human transplantation showed a more positive attitude among the respondents when considered a good organ transplantation solution. Conclusion: Flemish secondary school students favored the techniques of xenotransplantation to a lesser extent than allotransplantation; however, most of them did consider it a good solution for organ shortage. In comparison to animal‐to‐human transplantation, chimera‐to‐human transplantation showed a more positive attitude among the respondents when considered a good solution for organ transplantation.